بيت المقدس بين المسلمين والصليبيين خلال العصر الأيوبي (570 – 627 هـ/ 1174 – 1229 م) - زينب كريريش; د / قاوي محمد (جامعة عمار ثليجي الاغواط, 2023)
ملخص البحث: يتناول هذا البحث موضوع بيت المقدس بين المسلمين و الصليبيين خلال العصر الأيوبي (570- 627 هـ / 1174 – 1229م)، منذ تولي صلاح الدين الأيوبي لإدارة و قيادة الجيوش الإسلامية لمواجهة الغزو الصليبي إلى غاية وفاته ، بعد نجاحه في استرداد بيت المقدس و تحيرها في معركة حطين (583هـ/ 1187م). الهدف من هذه الدراسة هو التعمق في طبيعة العلاقات الأيوبية مع الصليبيين زمن صلاح الدين و الملك العادل و الملك الكامل من بعده، و يعنى هذا البحث بدراسة المواجهات العسكرية بين هؤلاء مع الصليبيين، و علاقاتهم الدبلوماسية على حد السواء، و من خلال تسليط الضوء على أهم المعارك ، و أهم المفاوضات و الاتفاقيات المبرمة . أتبعت في هذا البحث المنهج التاريخي الوصفي، و المنهج التحليلي المقارن، لكي الهدف من البحث، ثم جمع المادة العلمية للبحث من المصادر و المراجع العربية والبعض منها أجنبية ، و من خلال هذا البحث يتضح للباحث أن فترة حكم صلاح الدين و خوضها للمارك من أجل النصر و تحرير بيت المقدس، من أهم الفترات التي مرت بها الأمة الإسلامية و العالم ككل، من خلال ما أنجزه هذا القائد في انتصاراته الحربية ضد الصليبيين، و تعاملاته الدبلوماسية السلمية، و تمتعه بالذكاء الذي مكنه من إبرام المعاهدات، انعكست إيجابيا على مكانة دولته و حكمه، كما سيظهر للباحث أن تخاذل من جاء بعده إلى عرش الحكم خاصة الملك العادل و الملك الكامل قد غيرا في موازين القوى و الانحراف عن سياسة صلاح الدين التي تميزت بالجهاد و مواجهة العدو دون الإفراط في السلم الذي أدى إلى تسليم القدس في عهد الكامل. Searchsummary: This research deals with the issue of the Sacred House betweenMuslims and Crusadersduring the Ayubianera( 570-627 AH / 1174 – 1229 AD ), sinceSalahuddin Al-Ayoubitook over the management and command of Islamicarmies to confront the invasion Al-Sulaibiuntilhisdeath, afterhissuccess in recovering the holy house and bafflingit in the battle of Hattin ( 583 AH/ 1187 ). The aim of thisstudyis to delvedeeperinto the nature of the Cuban relations with the Crusaders at the time of Salah al-Din and the justking and the full kingafterhim, and this research isconcernedwithstudying the military confrontations betweenthese and the Crusaders، And theirdiplomatic relations alike, and by highlighting the most important battles, the most important negotiations and agreementsconcluded. I followed in this research the descriptive historicalapproach, and the comparative analyticalapproach, in order to aim the research, thencollect the scientificmaterial for research from Arab sources and references, some of which are foreign، And throughthis research itbecomesclear to the researcherthat the period of Salah al-Din’srule and itsfightagainst the Mark for victory and the liberation of the Holy House is one of the most important periodsthat the Islamic nation and the world as a whole have gone through،Throughwhatthis leader accomplished in hiswarvictoriesagainst the Crusaders, hispeacefuldiplomaticdealings, and hisenjoyment of the intelligence thatenabledhim to concludetreaties. I positivelyreflected on the position of his state and hisrule، It willalsoappear to the researcherthat the failure of thosewho came afterhim to the throne of government, especially the justking and the full king, has changed the balance of powers and deviatedfrom the policy of Salah al-Din, whichwascharacterized by jihad and confronting the enemywithout The excessive peacethatled to the handover of Jerusalemduring the reign of Kamel.
دراسة تحليلية ومقارنة